Perspektif Transmigrasi Jawa di Tinjau dari Komunikasi Terkait Konflik dan Rasisme di Desa Alue Leuhob Kabupaten Aceh Utara - Jamaluddin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This study discusses the perspective of the Javanese people who occupy Alue Leuhob Village, North Aceh Regency. The purpose is to describe, explain so that it becomes knowledge for the Indonesian people in general to briefly know the history of the conflict in terms of the communication that was built up to the emergence of negative views (racism) of the Acehnese people towards Javanese transmigration and the views of the objects in this study related to conflict at that time and post-conflict until now. This study uses a qualitative type with a descriptive form and is combined with an ethnographic approach that reconstructs the culture of a certain group of people. The results of the research during the conflict period that have been mentioned above show that: 1) Javanese people are very hated by GAM elements and by some Acehnese people who are victims of the Army on duty at that time. 2) Transmigration of Java must return to their hometown. 3) The Java transmigration food crisis resulted in famine. In the post-conflict period, namely: 1) Transmigration of Java and Aceh's security was at peace, referring to the Helsinki agreement. 2) the negative view of the Acehnese people who beat the average Javanese ethnicity has been minimized as evidenced by the fact that many Javanese are married to Acehnese. 3) Javanese Transmigration Have the same rights as citizens by having an ID card domiciled in Alue Leuhob Village, North Aceh Regency.